2000
DOI: 10.1006/bbrc.2000.2704
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Smad8 Phosphorylation Downstream of BMP Receptors ALK-2, ALK-3, and ALK-6 Induces Its Association with Smad4 and Transcriptional Activity

Abstract: Smads are intracellular signaling mediators for TGF-beta superfamily. Smad1 and Smad5 are activated by BMP receptors. Here, we have cloned mouse Smad8 and functionally characterized its ability to transduce signals from BMP receptors. Constitutively active BMP type I receptors, ALK-3 and ALK-6, as well as ALK-2, were phosphorylated Smad8 and induced Smad8 interaction with Smad4. Nuclear translocation of Smad8 was stimulated by constitutively active BMP type I receptors. In contrast, constitutively active TGF-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…The TGF-β type I receptors ALK4, ALK5, and ALK7 are not or are only inefficiently able to do this, which is consistent with the idea that Smad1 is a signaling mediator for BMP signals. Other investigators have suggested the same for Smad8 (23,24). This experiment ( Figure 3C) was performed in HEK 293T cells, which allow a reproducible high level of transgene expression.…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…The TGF-β type I receptors ALK4, ALK5, and ALK7 are not or are only inefficiently able to do this, which is consistent with the idea that Smad1 is a signaling mediator for BMP signals. Other investigators have suggested the same for Smad8 (23,24). This experiment ( Figure 3C) was performed in HEK 293T cells, which allow a reproducible high level of transgene expression.…”
Section: Figurementioning
confidence: 78%
“…Since Smad8 has been described as a Smad molecule that mediates BMP signals (23)(24)(25), and because the forced expression of full-length Smad8 in C3H10T1/2-BMP2 cells was unable to stimulate BMP2-dependent osteogenesis, we questioned whether Smad8 possesses biological activity or interferes with BMPdependent signalling. In the carboxyterminal end of its MH2 domain, Smad8 harbors an SSVS motif that has the potential to be phosphorylated for Smad activation (23,24). In the mesenchymal progenitor cell line C2C12, however, various types of BMPs activate overexpressed Smad8 only marginally (25).…”
Section: Figurementioning
confidence: 99%
“…However, the specific functional role of Smad8, which displays a high homology with Smad1 and Smad5, is not clear. Smad8 has been shown to be phosphorylated by ALK-2, ALK-3, and ALK-6 and thus acts as a downstream mediator for these receptors (53,76). Moreover, dominant-negative Smad8 was shown to inhibit the increase in alkaline phosphatase activity induced by BMP-2 in mesenchymal C3H10T1/2 cells and C2C12 myoblastic cells, indicating that Smad8 might play a role in this induction (53).…”
Section: Tgf-␤ Receptor Alk-5 Inhibits Maturation and Osteoblastic DImentioning
confidence: 99%
“…Smad8 has been shown to be phosphorylated by ALK-2, ALK-3, and ALK-6 and thus acts as a downstream mediator for these receptors (53,76). Moreover, dominant-negative Smad8 was shown to inhibit the increase in alkaline phosphatase activity induced by BMP-2 in mesenchymal C3H10T1/2 cells and C2C12 myoblastic cells, indicating that Smad8 might play a role in this induction (53). Recently, Aoki et al (16) reported that BMP-4 induces alkaline phosphatase activity equally well in the presence of Smad1, Smad5, and Smad8 in C2C12 cells.…”
Section: Tgf-␤ Receptor Alk-5 Inhibits Maturation and Osteoblastic DImentioning
confidence: 99%
“…Binding of BMPs to receptor complexes activates another subset of R-Smads, namely Smad1, Smad5 and Smad8 (Kawai et al, 2000;Meersseman et al, 1997). Unique to the Nodal system is the crucial requirement of a co-receptor from the EGF-CFC family -Cripto and Cryptic (Ding et al, 1998).…”
Section: Introductionmentioning
confidence: 99%